CR1 polymorphism in hydralazine-induced systemic lupus erythematosus: DNA restriction fragment length polymorphism. - Mitchell, J A (1989)
The contribution of genetic factors in the reduction in erythrocyte CR1 levels observed in hydralazine (Hz) induced systemic lupus erythematosus (SLE) was investigated by determining the frequency of a HindIII restriction fragment length polymorphism (RFLP) in the CR1 gene. This RFLP is associated with quantitative erythrocyte CR1 expression. Individuals who have developed SLE as a reaction to Hz therapy, consanguinous relatives of the Hz-SLE patients, controls who had been treated with Hz without any adverse reaction, and the consanguinous relatives of these controls were included in this study. No difference was found in the frequency of occurrence of the alleles associated with CR1 expression between the Hz-SLE patients and the control groups (P greater than 0.2). Individuals from the Hz-SLE group who were homozygous for the 7.4 kb 'high expressor' allele had lower mean levels of erythrocytes CR1 (564 +/- 65) than the corresponding homozygous subgroups within the Hz-SLE relative group (774 +/- 46), the Hz control group (756 +/- 80) and the Hz control relatives group (825 +/- 66). In addition, 50% of the Hz-SLE patients in the 'high expressor' subgroup who had less than 500 CR1 per erythrocyte had elevated levels of circulating immune complexes. This study suggests that individuals who are genetically low expressors of erythrocyte CR1 are not predisposed to developing SLE in response to Hz therapy, and that in a subgroup of genetically 'high expressors', low CR1 levels are associated with elevated levels of circulatory immune complexes.